Galectins as New Prognostic Markers and Potential Therapeutic Targets for Advanced Prostate Cancers - Laderach, Diego J. (Hindawi Publishing Corporation, 2013)
A better understanding of multimolecular interactions involved in tumor dissemination is required to identify new effective therapies for advanced prostate cancer (PCa). Several groups investigated protein-glycan interactions as critical factors for crosstalk between prostate tumors and their microenvironment. This review both discusses whether the “galectin-signature” might serve as a reliable biomarker for the identification of patients with high risk of metastasis and assesses the galectin-glycan lattices as potential novel targets for anticancer therapies. The ultimate goal of this review is to convey how basic findings related to galectins could be in turn translated into clinical settings for patients with advanced PCa.